2017
DOI: 10.1259/dmfr.20160315
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exposure parameters and slice thickness on detecting clear and unclear mandibular canals using cone beam CT

Abstract: Objectives: The purpose of this study was to clarify the effects of exposure parameters and image-processing methods when using CBCT to detect clear and unclear mandibular canals (MCs). Methods: 24 dry half mandibles were divided into 2 groups with clear and unclear MCs based on a previous CBCT study. Mandibles were scanned using a CBCT system with varying exposure parameters (tube voltages 60 kV, 70 kV and 90 kV; and tube currents 2 mA, 5 mA, 10 mA and 15 mA) to obtain a total of 144 scans. The images were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 30 publications
(43 reference statements)
2
17
1
Order By: Relevance
“…In Experiment 1, the Az values increased as the voltage increased. This result supports the findings of Jasa et al 15 . We next assessed the correlation between the number of holes obtained from our previous study and the Az values from the ROC analysis.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In Experiment 1, the Az values increased as the voltage increased. This result supports the findings of Jasa et al 15 . We next assessed the correlation between the number of holes obtained from our previous study and the Az values from the ROC analysis.…”
Section: Discussionsupporting
confidence: 93%
“…The number of extracted holes and the Az values of clear ( Figure 7a) and unclear ( Figure 7b) MCs obtained in the previous study 15 The number of holes and the Az value increased under better scanning conditions in both Experiments 1 and 2. In particular, images with more than 70 extracted holes corresponded almost exactly with the Az values of more than 0.8.…”
Section: Experiments 2: Relationship Between the Detectability Of The supporting
confidence: 50%
See 2 more Smart Citations
“…However, several studies demonstrated different conclusions on the dependence of the slice thickness of CBCT scans and the detection of the anatomical and other structures, as well as the way that reduces artefacts [18][19][20][21][22][23][24]. Our choice of slice thickness was 1 mm for good and moderate detection of CS without missing it and with high reduction of artefacts in this case.…”
Section: Discussionmentioning
confidence: 81%